Improvement of mild photoaged facial skin in middle‐aged Chinese females by a supramolecular retinol plus acetyl hexapeptide‐1 containing essence - Ying Ye; Yanan Li; Chenlan Xu; Xiaolan Wei (Wiley, 2023)
Abstract Background The anti‐ageing gold standard, retinol, has been widely recognized for its anti‐wrinkle benefits in the Chinese population. Studies have shown that Asians are more sensitive to retinol compared to their Caucasian counterparts, and it is generally recommended to use retinol once a day in the evening. However, there are few reports on the most appropriate concentration and frequency of retinol use in the general Chinese population. Objectives In this study, supramolecular retinol was prepared using cyclodextrin encapsulation technology, and the most appropriate concentration for the general Chinese population was investigated. Then, a cosmetic essence was developed by combining the classic supramolecular retinol, which promotes collagen regeneration, with acetyl hexapeptide‐1, a popular ingredient known for reducing expression lines. The safety and efficacy of this cosmetic essence were studied through clinical tests. Methods First, a patch test was conducted on 32 healthy Chinese subjects to compare the tolerance of supramolecular retinol to non‐encapsulated retinol and to select the optimal concentration of retinol. Then, an 8‐week clinical study was conducted using a twice‐daily cosmetic essence containing 0.1% supramolecular retinol and 0.02% acetyl hexapeptide‐1 to treat mild photoaging in 32 middle‐aged Chinese women. Dermatological evaluations and instrument measurements were taken at baseline, 4 weeks, and 8 weeks. Efficacy was assessed using facial skin wrinkles, textures, elasticity, firmness, pores, gloss and stratum corneum hydration. Tolerability was assessed throughout the study. Results Our patch test results showed that supramolecular retinol was better tolerated than non‐encapsulated retinol, and our findings suggest that 0.1% was the approximate optimal retinol concentration for the general Chinese population. The cosmetic essence studied was effective in improving the appearance of photoaged skin in the Chinese population in all aspects studied and was well tolerated. Conclusions 0.1% retinol is suitable for twice daily use in the general Chinese population. Data and records on efficacy dimensions of skin textures, elasticity, firmness, pores, gloss and stratum corneum hydration for retinol in the Chinese population are supplemented with our study. Cosmeceutical approaches targeting both static and dynamic wrinkles are of value for treating the photoaged Chinese population.